التوظيف السياسي لمفهوم الكفر عند الجماعات المتطرفة- قراءة نقدية في ضوء القرآن الكريم والسنة المطهّرة - العسكري, ساجد صباح ميّس; العنبكي, سجاد هادي صاحب (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Atonement is one of the important jurisprudential and doctrinal topics, and it has taken up a large area of writings by those interested in the two fields, and many seminars and conferences have been held for this purpose, due to the jurisprudential and doctrinal issues that it entails. very dangerous It threatens the entity and stability of society, and destroys the walls of peaceful coexistence, destroying what was built and restored before Reformers over time. The research entitled (The Political Employment of the Concept of Disbelief among Extremist Groups); To show the problem of not distinguishing between establishment and employment. The Holy Qur’an and the Noble Sunnah did not establish the killing of the infidel, but rather they established the foundations for peaceful coexistence. With the other, but the problem lies in employing the concept of disbelief politically to be an oppressive tool in the hands of extremist groups. The research was divided into two sections. The first: a theoretical study on the concept of disbelief points. He discussed the definition of disbelief and its control in language, Quranic usage, and jurisprudential terminology. Second: Methods of political exploitation of the concept of disbelief. Among the most important of these methods: not distinguishing between disbelief in the specific sense and disbelief in the more general sense, and relying on weak hadiths and wrong interpretation of noble texts. We have made an effort to clarify this problem, and if we succeed in doing so, praise be to God first and last, even if there is a deficiency or defect in it. This is one of the characteristics of the possible, so we ask you for an excuse. May God grant us success in all goodness and righteousness.